Plant Health Innovation Platform at Qob Elias, Lebanon: farmer participatory approaches for wide dissemination of pest management innovations - Kumari, Safaa; Choueiri, Elia; Moukahel, Abdulrahman; Jreijiri, Fouad; Massaad, Randa; Al Zammar, Souheir; Wakim, Samer; Chaalan, Zainab; Abou Yaghi, Diana; Darwish, Iman; Kemal, Seid Ahmed (International Center for Agricultural Research in the Dry Areas, 2023)
Integrated pest and disease management (IPDM) represents a range of environmentally-sound approaches to crop protection and is increasingly recognized as an essential component of sustainable agricultural development. To promote the use of IPDM, it is necessary to validate and disseminate effective IPDM options to farming communities. To this end, the CGIAR Plant Health Initiative (PHI) has initiated nine Innovation platforms (IPs) in Africa, Asia, and Latin America, to develop and validate pest management solutions for major crops in real-life environments. One of these IPs was launched in Lebanon (Qob Elias Village, Beqaa Valley). The PHI-IP plays a key role in the participatory analysis of pest constraints, validation of farm-level pest management options, and scaling innovation broadly to reduce productivity and quality losses and increase the incomes of rural farming communities. The PHI-IP brought key partners together and provided solutions to the existing production challenges. IP is one of the approaches to validate innovations and getting feedback from users. The primary purpose of these PHI-IPs is to co-create and/or identify/validate IPDM packages that are highly effective and affordable. This is done with the engagement of multiple and relevant institutions, including CGIAR, IARCs, NARES and private sector partners. The identified IPDM packages coming out of this work at the Innovation Platform can then be potentially scaled up/deployed in farmers’ fields. These platforms can also serve to demonstrate the efficacy of identified IPDM packages to diverse stakeholders, including farmers and policy makers, in addition to providing an opportunity for training/capacity strengthening of partners, including young researchers.